Wild small mammals in intensive milk cattle and swine production systems - Lovera, Rosario (2015)
Some rodent species are considered important pests around the world because they cause economic losses and sanitary problems. Although rodents are found in many different environments, they select habitat patches where resources are available. There is scant information regarding community composition and habitat distribution of small mammals in dairy and pig production systems. The aim of this research was to compare the composition of wild small mammal communities between intensive dairy and pig farms and to describe their distribution among habitats within the farms in northeast Buenos Aires province, Argentina. The intent is to contribute to management strategies of small mammals in these production systems. Ten pig farms and eight dairy farms were sampled seasonally during one year. Cage and Sherman live traps were set in five habitats within the farms. A total of 505 small mammals (270 in dairy farms and 235 in pig farms) were captured in 7026 cage trap-nights and 7333 Sherman trap-nights. In both production systems, the rodents captured included the dominant murines: Rattus norvegicus, R. rattus and Mus musculus, native sigmodontines: Azodon azarae, Calomys laucha and Oligoryzomys flavescens and the native caviid Cavia aperea. The opossums Didelphis albiventris and Lutreolina crassicaudata were also captured. The introduced murines used mainly human buildings, food storage sheds and animal sheds, whereas native species were more common in the vegetated environments among dwellings. A recommendation for control of pest rodent species would be to apply rodenticides only in dwellings to avoid accidental poisoning of non-target native species. Further studies on the damage produced by small mammal species and their role in the disease transmission in these production systems are necessary to identify management priorities.